PENENTUAN BESAR ENERGI LISTRIK AKI DENGAN MEMVARIASIKAN JUMLAH AIR SULING (H2O) DAN ASAM SULFAT (H 2SO4 ) - Romadona '; Maksi Ginting; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been conducted to determine electrical energy of accu with variation of volume of distilled water and sulfuric acid. In this study, an electrolyte solution of 400 ml was prepared for each accu consisting of a mixture of distilled water and sulfuric acid with different compositions. Measurements of each sample were carried out at the interval time of 15 minutes for 2 hours. The results showed that the amount of energy produced by accu with a standard electrolyte solution expenses factory for 2 hours was 114.14 kilojoules. The amounts of energy obtained from the variation of the mixture composition of the electrolyte solution ratio were 154.23 kilojoules, 156.73 kilojoules, and 141.61 kilojoules, respectively for a mixture of distilled water and sulfuric acid witha composition ratio of 64% : 36%, 60% : 40%, and 70% : 30%, where as for a mixed electrolyte solution with aquabides and sulfuric acid, resulted the energy of 164.18 kilojoules, 157.37 kilojoules, and 148.52 kilojoules, respectively for the mixture ratio of 64% : 36%, 60% : 40%, and 70% : 30%. Conclusion, the largest energy produced was obtained by the accu with electrolyte solution containing a mixture of sulfuric acid and aquabides with the composition ratio of 64% : 36%.